The structural evolution of light-ion implanted 6H-SiC single crystal: Comparison of the effect of helium and hydrogen. (15th April 2020) - Daghbouj, N.; Li, B.S.; Callisti, M.; Sen, H.S.; Lin, J.; Ou, X.; Karlik, M.; Polcar, T.
Abstract: The microstructure evolution of hydrogen-implanted 6H-SiC at different temperatures and fluences is investigated by using various experimental techniques. In H-implanted samples with relatively low fluence at RT, dense blister cavities are observed after annealing at 1100 °C, while no visible blister cavities appear after annealing at 1100 °C in the sample implanted at RT with high fluence. The absence of blister cavities is due to the loss of elastic energy during the crystalline-to-amorphous transition. With a further increase of implantation temperature to 450 and 900 °C, amorphization did not occur and H-containing microcracks grew laterally below the surface. Thus, blisters appeared on the surface of the samples implanted at 900 °C even without annealing. The results are compared to the microstructural evolution of He-implanted 6H-SiC which was explored in our previous work. The behavior of hydrogen and helium ions in 6H-SiC lattice was rather different. For He implantation, regardless of the fluence and implantation temperature, blisters did not form. The mechanism of migration and coalescence of nanoscale bubbles that are responsible for blistering were studied via density functional theory calculations, which well-supported the presented results. We found that both mechanisms (migration and coalescence) are energetically cheaper in the case of H compared to He. Graphical abstract: Image, graphical abstract